MYCOBACTERIOSIS IN THE PRACTICE OF PULMONOLOGISTS AND PHTHISIOLOGISTS - A. E. Ergeshov; E. I. Shmelev; M. N. Kovalevskaya; N. L. Karpina; E. E. Larionova; L. N. Chernousova (Туберкулез и болезни лёгких)
Goal of the study: to investigate the frequency of mycobacteriosis in the practice of pulmonologists and phthisiologists.Materials and methods. The analysis included medical files of 156 patients with various non-specific respiratory diseases and tuberculosis who were examined in 2011-2014 and non-tuberculous mycobacteria were found in their sputum.Results of the study. pulmonary mycobacteriosis was diagnosed in 93 (59.6%) patients out of 156 who corresponded the criteria of American Thoracic Society and etiotropic treatment was prescribed. While detection of non-tuberculous mycobacteria in the other patients was considered as innidiation of respiratory tract by those mycobacteria in case of chronic non-specific pulmonary disease and/or tuberculosis. Mycobacterioses were treated with the relevance to drug susceptibility of the causative agent and there were numerous obstacles due to high frequency of adverse reactions.